Differential diagnosis of cardiac tumors: General consideration and echocardiographic approach. Issue 8 (11th October 2022) - Pino, Paolo G.; Moreo, Antonella; Lestuzzi, Chiara
Abstract: Cardiac tumors may be primary (either benign or malignant) or secondary (malignant) and are first detected by echocardiography in most cases. The cardiologist often challenges their identification, the differential diagnosis and the best therapeutic approach. Malignant tumors have usually a poor prognosis, which may be significantly improved by appropriate and timely therapies. The echocardiographic aspects of benign and malignant cardiac tumors described in this article, along with a clinical evaluation may orient the differential diagnosis and aid in choosing the further steps useful to define the nature of the mass, Abstract : All the malignant and some benign cardiac have a dismal prognosis without a prompt treatment. Correctly recognizing cardiac tumors and assessing their potential clinical risks is of utmost importance. The clinical aspects and echocardiographic information should be integrated to plan the diagnostic and therapeutic pathways.